Posture and gesture - Bull, Peter, 1949- (International series in experimental social psychology, 1987)
This volume presents the results of a series of studies carried out by the author focusing on the role of posture and gesture in interpersonal communication. The first section of the book sets these studies in the general context of non-verbal communication research; in addition, previous research on posture and gesture is reviewed in order to highlight the particular issues which were chosen as the focus of research reported here. In Part II, six experiments are presented concerning the extent to which posture communicates information about listener emotions and attitudes. The seven studies r.